How to Control Children's Consumption Behavior? - Sa'adah, Silky Roudhotus; Najib, M. Thoha Ainun (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2024)
This study aims to find out how parents internalize the control of consumption behavior of elementary school age children (7 -12 years). This research uses qualitative research with exploratory descriptive approach. Participants in this study were 200 elementary school students aged 7-12 years. Data was collected through interview, observation, and documentation techniques and analyzed. The results showed that the internalization of wise consumption as a control of children's consumption behavior was carried out by 1) Habitating relevant actions, 2) Introducing money from an early age, 3) Providing verbal explanations to children, 4) Giving direct examples to children, 5) Teaching manage finances to children from an early age, 6) Teach children about rationality in consumption, 7) Children are taught how to make economic decisions, 8) Give children confidence in financial management, 9) Discuss the use of money between children and parents, 10) Familiarize children to live economically from an early age, 11) Teach children to save.